Risk Factors for Allergic Rhinitis in Students of SMA Negeri 1 Padang, Indonesia - Hidayat, Rachmat; Sari, Puspa (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Allergic rhinitis (AR) is a disorder of the nasal mucosa caused by inflammation and initiated by a hypersensitivity reaction due to exposure to allergens. This study aimed to determine the risk factors associated with allergic rhinitis in SMA Negeri 1 Padang Indonesia students. Methods: This study was an observational study with a cross-sectional approach. A total of 500 research subjects participated in this study, and the research subjects met the inclusion criteria. The inclusion criteria were SMA Negeri 1 Padang, Indonesia students aged 15-17 years and willing to participate in the research as evidenced by the consent of their parents or guardians to participate in this study. Data analysis was carried out using SPSS software version 25. Univariate analysis was performed to present the frequency distribution of each variable test. Bivariate analysis was performed to determine the relationship between risk factors and incidence of rhinitis allergies, p < 0.05. Results: The results of the study show that gender is not related to the incidence of rhinitis allergies. Smoke exposure, owning pets, dust exposure, and a history of atopy are associated with events of rhinitis allergies, p<0.05. Conclusion: Smoke exposure, owning pets, dust exposure, and a history of atopy are risk factors for this incidence of allergic rhinitis in SMA Negeri 1 Padang, Indonesia students.